Asarones from Acori Tatarinowii Rhizoma stimulate expression and secretion of neurotrophic factors in cultured astrocytes. (10th August 2019) - Lam, Kelly Y.C.; Wu, Qi-Yun; Hu, Wei-Hui; Yao, Ping; Wang, Huai-You; Dong, Tina T.X.; Tsim, Karl W.K.
Graphical abstract: Highlights: α-Asarone and β-asarones derived from Acori Tatarinowii Rhizoma stimulates the expression and secretion of neurotrophic factors in cultured astrocytes. α-Asarone and β-asarone activated PKA signaling, which subsequently triggered the expression of neurotrophic factor promoters The neuro-beneficial effect of asarone offers an exciting therapeutic approach to a number of neuronal diseases. Abstract: Acori Tatarinowii Rhizoma (ATR, the dried rhizome of Acorus tatarinowii Schott.) is a traditional Chinese medicine widely used to treat brain diseases, e.g. depression, forgetfulness, anxiety and epilepsy. Several lines of evidence support that ATR has neuronal beneficial functions in animal models, but its action mechanism in cellular level is unknown. Here, we identified α-asarone and β-asarone could be the major active ingredients of ATR, which, when applied onto cultured rat astrocytes, significantly stimulated the expression and secretion of neurotrophic factors, i.e. nerve growth factor (NGF), brain derived neurotrophic factor (BDNF) and glial derived neurotrophic factor (GDNF), in dose-dependent manners. These results suggested that the neuronal action of ATR, triggered by asarone, might be mediated by an increase of expression of neurotrophic factors in astrocytes, which therefore could support the clinical usage of ATR. In addition, application of PKA inhibitor, H89, in cultured astrocytes partially blocked the asarone-induced neurotrophic factor expression, suggesting the involvement of PKA signaling. The results proposed that α-asarone and β-asarone from ATR could serve as potential candidates for drug development in neurodegenerative diseases.